The Effect of Progressive Muscle Relaxation Technique on Fatigue, Pain and Quality of Life in Dialysis Patients: A Clinical Trial Study - Mojtaba Khazaei Ghozhdi; Mahnaz Ghaljeh; Negin Khazaei (Mashhad University of Medical Sciences, 2023)
Background: Fatigue and pain are of the most common symptoms in dialysis patients affecting their quality of life (QoL). One of the methods to reduce pain and fatigue is the use of complementary therapies.Aim: This study was performed aimed to determine the impact of progressive muscle relaxation on fatigue, pain and QoL of dialysis patients.Method: This clinical trial study was performed on 60 patients undergoing dialysis in Zahedan, Iran, 2021. The subjects were randomly assigned to the intervention and control groups (n=30 in each group). Data collection tools included a demographic form, Fatigue Severity Scale (FSS), pain visual scale, dialysis quality of life questionnaire (KDQOL-SF), and a self-control checklist. In the intervention group, a progressive muscular relaxation was done in three training sessions for an hour by the researcher. The intervention group was asked to perform relaxation technique at home twice a day for 12 weeks. The control group received no intervention. Data were analyzed by SPSS (version 21). P<0.05 was considered statistically significant.Results: The mean scores of fatigue, pain, QoL and its dimensions showed no significant difference between the two groups before the intervention (P>0.05). However, three months after progressive muscle relaxation technique, the two groups were significantly different in terms of the mean scores of fatigue, pain, and QoL (P<0.05).Implications for Practice: The implementation of the relaxation technique reduces fatigue and pain and develops QoL of dialysis patients. Progressive muscle relaxation technique is recommended to be used as an intervention in nursing care.